Relevance of the spatial triad theory in (re) designing and planning of academic library spaces - Ilako, Caroline; Maceviciute, Elena; Bukirwa, Joyce M (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
Henri Lefebvre (1991) ,  spatial triad of interconnected ‘moments’ in the production of space and applies it to library spaces. His conceptualization of space portrays it as a ‘social product’ and that human experiences are socially produced within the spaces that they occupy. He argues that space consists of three elements i.e. spatial practice (perceived space), representations of space (conceived space) and representational spaces (lived space). Perceived- conceived-lived spaces have a dialectical relationship with one another and therefore call for proper analysis by the library managers who are planning on new spaces or on remodelling the existing spaces. These three elements will be operationalized as representations of space (library space attributes) influences different spatial practices (user perception, preferences and behavior) and representational space (user experience, satisfaction and factors affecting use) within library spaces. They constitute the analytical basis for designing and planning spaces for all types of libraries.  This article constitutes the theoretical position regarding the three spatial triad elements and their implications on library spaces.